1991
DOI: 10.1203/00006450-199104000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Constitutionally Short Stature: Analysis of the Insulin-Like Growth Factor-I Gene and the Human Growth Hormone Gene Cluster

Abstract: ABSTRACT. It has been suggested that modifications of the IGF

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 15 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Probes ' random primer labelled probes for the protein coding regions of IGFBP-1 (350 bp), IGFBP-2 (446 bp), IGFBP-3 (475 bp) (Bnnkman et al 1988, Bmkert et al 1989, and IGF-I Ea (725 bp) (Mullís et al 1991) were used. For non-isotopic in situ hybridisation ex¬ periments, anti-sense and sense digoxigenin-labelled probes were made by in vitro transcription with SP6 or T7 RNA polymerase after digestion with Smal or EcoRV respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Probes ' random primer labelled probes for the protein coding regions of IGFBP-1 (350 bp), IGFBP-2 (446 bp), IGFBP-3 (475 bp) (Bnnkman et al 1988, Bmkert et al 1989, and IGF-I Ea (725 bp) (Mullís et al 1991) were used. For non-isotopic in situ hybridisation ex¬ periments, anti-sense and sense digoxigenin-labelled probes were made by in vitro transcription with SP6 or T7 RNA polymerase after digestion with Smal or EcoRV respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The IGF1 locus has been extensively analyzed in several groups of children with "idiopathic" congenital growth retardation; however, no mutations have been identified, leading to the suggestion that IGF-I mutations are not a common cause of growth retardation in humans (145)(146)(147). The debate has been rekindled by the identification of a single case of human IGF1 knockout due to a partial deletion of IGF1.…”
Section: Developmental Phenotypes Of Humans Lacking Igf-i or Igf1rmentioning
confidence: 96%
“…IGF-I synthesis Ours and many laboratories have made intense searches to find gene alterations of the IGF-I gene causing GH resistance (189,190). In 1996, Woods et al (152) reported a patient, a 15 year old boy, who had severe intrauterine and postnatal growth retardation, sensorineural deafness, mental retardation and hyperactivity, due to a homozygous deletion of exons 4 and 5 of the IGF-I gene (152).…”
Section: Primary Defects In Igf-imentioning
confidence: 99%